ANALISIS TINGKAT KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK DALAM MEMECAHKAN MASALAH GEOMETRI DITINJAU DARI GAYA BELAJAR KELAS X MATEMATIKA ILMU ALAM (MIA) 4 SMA NEGERI 2 SRAGEN TAHUN PELAJARAN 2014/2015 - Iswanti, Partia; Riyadi, Riyadi; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to analyze the level of creative thinking abilities of students withÂ  visual, auditorial and kinesthetic learning styles types in solving geometry problems. The level creative thinking abilities compared were the level 4 (very creative), the level 3 (creative), the level 2 (enough creative), the level 1 (less creative), the level 0 (not creative). This research was a qualitative research. The subject of this research was 6 students from the grade X MIA 4 of National High School 2 Sragen in Academic Year 2014/2015. The Subject of this research was selected used purposive sampling technique. Data collection was done by interview based task, the subject were asked to express verbally and write the answer what the subject thinks. The main instrument in this research was the researcher themselves, assisted by three instruments form of geometry problem solving test, interview guide and questionnaire learning styles. The validity of data used time triangulation. The results of this research were as follows. (1) The students with visual learning styles types was in creative thinking abilities on the level 3 (creative) and level 4 (very creative). The students with visual learning styles types was able to show creative thinking abilities on aspect of fluency, flexibility and novelty. (2) The students with auditorial learning styles types was creative thinking abilities on the level 3 (creative). The students with auditorial learning styles types was able to show creative thinking abilities on aspect of fluency and flexibility. (3) The students with kinesthetic learning styles types was creative thinking abilities on the level 2 (enough creative) and level 1 (less creative). The students with kinesthetic learning styles types was able to show creative thinking abilities on aspect of flexibility and fluency.Keywords: Level of Creative Thinking Abilities, Geometry Problem Solving, Learning Styles.Â